2005
DOI: 10.1136/ard.2004.026773
|View full text |Cite
|
Sign up to set email alerts
|

Proton magnetic resonance spectroscopy may predict future brain lesions in SLE patients: a functional multi-imaging approach and follow up

Abstract: Objective: To determine whether single photon emission tomography (SPECT) and magnetic resonance spectroscopy ( 1 H-MRS) can predict the appearance of new lesions in systemic lupus erythematosus (SLE), detectable by magnetic resonance imaging (MRI). Methods:99 Tc m -HMPAO-SPECT, brain MRI, and 1 H-MRS were done in eight women with SLE (mean age 31.8 years; disease duration 5.5 years). NAA/Cho, NAA/Cre, and Cho/Cre ratios were assessed in hypoperfused and normoperfused areas detected by SPECT that were normal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 29 publications
(28 reference statements)
1
33
1
Order By: Relevance
“…However, the structural MRI has been found to be of limited value in patients with diffuse neuropsychiatric disturbances such as headache, cognitive dysfunction, affective disorders, and confusional states [Rozell et al, 1998;Sabet et al, 1998]. Multiple functional neuroimaging modalities have therefore been used in SLE, including 1 H-magnetic resonance spectroscopy (MRS) [Castellino et al, 2005], SPECT [Appenzeller et al, 2007a], and fMRI [DiFrancesco et al, 2007;Fitzgibbon et al, 2008;Rocca et al, 2006]. These studies have suggested that functional alterations could precede structural changes in NP-SLE [Castellino et al, 2005], and, moreover, they allowed differentiation between patients with or without active CNS involvement [Appenzeller et al, 2007a].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the structural MRI has been found to be of limited value in patients with diffuse neuropsychiatric disturbances such as headache, cognitive dysfunction, affective disorders, and confusional states [Rozell et al, 1998;Sabet et al, 1998]. Multiple functional neuroimaging modalities have therefore been used in SLE, including 1 H-magnetic resonance spectroscopy (MRS) [Castellino et al, 2005], SPECT [Appenzeller et al, 2007a], and fMRI [DiFrancesco et al, 2007;Fitzgibbon et al, 2008;Rocca et al, 2006]. These studies have suggested that functional alterations could precede structural changes in NP-SLE [Castellino et al, 2005], and, moreover, they allowed differentiation between patients with or without active CNS involvement [Appenzeller et al, 2007a].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple functional neuroimaging modalities have therefore been used in SLE, including 1 H-magnetic resonance spectroscopy (MRS) [Castellino et al, 2005], SPECT [Appenzeller et al, 2007a], and fMRI [DiFrancesco et al, 2007;Fitzgibbon et al, 2008;Rocca et al, 2006]. These studies have suggested that functional alterations could precede structural changes in NP-SLE [Castellino et al, 2005], and, moreover, they allowed differentiation between patients with or without active CNS involvement [Appenzeller et al, 2007a]. Moreover, NP-SLE patients exhibited greater activation of specific cerebral regions than healthy controls in tasks of working memory [Fitzgibbon et al, 2008], motor control [Rocca et al, 2006], and attention and language processing [DiFrancesco et al, 2007], possibly indicative of functional compensation in NP-SLE patients that could reflect impairment of cerebral functions relating to these tasks.…”
Section: Discussionmentioning
confidence: 99%
“…This study did include APS patients and corroborated the impression of subclinical neuronal damage induced by disease activity [15]. When multimodal imaging techniques are used assessing not only neurometabolic patterns (MR spectroscopy), but also perfusion (SPECT) and morphological abnormalities (conventional MRI), the predictive power seems to be increased and might be justified in selected clinical cases in an attempt to modify the course of the disease [16].…”
Section: Evidence From Neuroimagingmentioning
confidence: 83%
“…In that study metabolic changes at the basal ganglia, besides the normal appearing white matter, was also found, indicating small vessel injury. Reduction of NAA/Cr ratio and elevation of Cho/Cr ratio in normal appearing white matter, related to the severity of neuropsychiatric symptoms was also proved by others (Axford et al, 2001;Handa et al, 2003;Castellino et al, 2005). Axford and co-workers also performed quantitative absolute assessment of the metabolites and found increased absolute concentration of mI in NPSLE patients symptoms, that could be the result of inflammation, with a trend to be reversible in patients with minor.…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 93%